Innovative Approach to Crew and Passenger Health during Flight - Maria-Aida STAN; Mioara DUCA; Narcisa VALTER; Iulian DUCA; Vlad TURCANU (Communications of International Proceedings, 2020)
There are numerous health-related issues that can occur during flight, for both passengers and crew members. The incidence of these issues rises for those who fly frequently. Among these risks are noise-related stress and frequent exposure to radiation, both ionizing, in the form of cosmic radiation and non-ionizing, in the form of UV rays. Numerous studies have correlated exposure to radiation with increased risk of developing several illnesses, especially cancer. Noise has also been documented to produce physical, physiological and mental effects on individuals. This paper aims to provide an overview of literature regarding this problem in order to highlight its importance and to propose several solutions that could alleviate the issue. Regarding cosmic radiation, we propose shielding the inner fuselage of aircraft in order to reduce the amount of radiation that enters the plane. We analyze the viability of this solution regarding added mass and shielding capability. We also touch briefly upon Z-grade materials, that are used in shielding satellites and that could be used in shielding aircraft as well. Regarding UV rays, we have found a simple and cost-effective solution, which can block UV rays without reducing windshield visibility.
Keywords: Radiation; Aviation; Health; Ergonomics.